The emergence of the occupational health and safety profession in Australia. (August 2019) - Provan, David J.; Pryor, Pam
Highlights: The OHS profession has established itself within Australia over the past 30 years. The Safety Institute of Australia has implemented a professionalisation strategy. The OHS profession requires a joint effort of government, universities and industry. The OHS profession requires regulation of obligations, education, and licencing. Abstract: The Occupational Health and Safety (OHS) profession is well established in Australia and it would be rare, if not impossible to find a medium to a large public, private or government organisation without an OHS professional department. This paper explores the development and current status of the OHS profession in Australia. To be recognised as a profession, any occupation needs to satisfy a number of individual, collective and external professional criteria. This paper reviews the OHS profession in Australia, through these professional criteria and we describe the: role and career path, defined knowledge and skill base, ethical code of practice, professional status, professional organisations, professional entry criteria, professional education, external requirements, stakeholders, and societal recognition. To further examine the extent to which the OHS occupation deserves professional status we explore in detail the professionalisation strategy of the Safety Institute of Australia (SIA) over the past 8 years. Since 2010 the Safety Institute of Australia (SIA), the largest and broadest Australian OHS professional organisation, has rigorously pursued a strategy aimed at increasing the professionalisation of the OHS profession through concurrent programs of: professional certification, university curriculum accreditation, and the development of an 'OHS Body of Knowledge'. This paper concludes that the OHS profession in Australia can be considered an 'emerging profession'. An emerging profession is a recognised discipline or occupation that has established, although not consistently implemented the structures, capability and recognition necessary to be considered an established profession. The current and future challenges and opportunities for the OHS profession are discussed.